Proposing an information value chain to improve information services to disabled library patrons using assistive technologies. (December 2022) - Potnis, Devendra; Mallary, Kevin
Information services offered by academic libraries increasingly rely on assistive technologies (AT) to facilitate disabled patrons' retrieval and use of information for learning and teaching. However, disabled patrons' access to AT might not always lead to their use, resulting in the underutilization of information services offered by academic libraries. We adopt an inward-looking, service innovation perspective to improve information services for disabled patrons using AT. The open coding of qualitative responses collected from administrators and librarians in 186 academic libraries in public universities in the United States, reveals 10 mechanisms (i.e. modified work practices), which involve searching, compiling, mixing, framing, sharing, or reusing information, and learning from it. Based on this information-centric reorganisation of work practices, we propose an 'information value chain', like Porter's value chain, for improving information services to disabled patrons using AT in academic libraries, which is the major theoretical contribution of our study.